2015
DOI: 10.1007/s13277-015-3609-6
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of Nemo-like kinase expression in patients with hepatocellular carcinoma

Abstract: Nemo-like kinase (NLK) is an evolutionarily conserved serine/threonine protein kinase and belongs to the extracellular signal-regulated kinases/microtubule-associated protein kinase families (Erks/MAPKs). Previous studies have indicated that abnormal expressions of NLK played critical roles in various types of human cancers. Recent studies suggested that NLK expression was significantly upregulated in the hepatocellular carcinoma (HCC) specimens. However, the clinical significance of NLK expression in HCC rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…NLK has been demonstrated to correlate with histological grade, advanced stage, and lymph node metastasis. 14 , 15 , 17 , 21 Similarly, our study suggests that tumors with high NLK expression had greater invasive potential including vascular/lymphatic invasion. NLK overexpression was also observed in high-invasive regions such as metastatic lymph node.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…NLK has been demonstrated to correlate with histological grade, advanced stage, and lymph node metastasis. 14 , 15 , 17 , 21 Similarly, our study suggests that tumors with high NLK expression had greater invasive potential including vascular/lymphatic invasion. NLK overexpression was also observed in high-invasive regions such as metastatic lymph node.…”
Section: Discussionsupporting
confidence: 59%
“…Subcellular fractionation from COS7 cells and HEK293 cells verifies that ~60%–70% of NLK is localized in the nucleus and 30%–40% is localized in the cytoplasm. 20 NLK was predominantly located in the nucleus of tumor cells in nasopharyngeal carcinoma, hepatocellular carcinoma, glioma, and gallbladder cancer; 10 , 14 , 15 , 17 however, NLK was expressed mainly in the cytoplasm of tumor cells in colorectal cancer. 21 NLK-positive staining was confined mainly to the nucleus and cytoplasm in non-small-cell lung cancer (NSCLC).…”
Section: Discussionmentioning
confidence: 98%
“… 23 , 24 Unfortunately, there was no significant downregulation of DKK3 and NLK in HCC tissues compared with ANLTs (data not shown), which was consistent with the results from previous reports. 25 , 26 , 27 Neither DKK3 nor NLK had the inverse relationship with miR-92b expression in HCC tissues, implying DKK3 and NLK might not be key downstream targets of miR-92b in HCC progression. In view of the fact that one miRNA might downregulate large numbers of target genes by binding to complementary sequences in the 3′-UTR of target mRNAs, the downstream targets of a miRNA in one particular tissue or cell type should be determined by the gene expression patterns specific to the tissue or cell.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have suggested that Edmondson-Steiner grade is an independent factor affecting prognosis/recurrence of HCC [ 15 – 20 ], which should be taken into account when considering therapeutic strategy [ 16 , 19 ]. In addition, liver cells take up Gd-EOB-DTPA via the receptors OATP1B1, OATP1B3 and NTCP.…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that Edmondson-Steiner grade was an independent predictor for early recurrence in HCC. Furthermore, Edmondson-Steiner grade has been shown to be related to other markers of poor prognosis, including microvascular invasion [ 15 – 19 ], expression of Nemo-like kinase (NLK), Protein disulfide isomerase (PDI), p21-activated protein kinase (PAK) 6, chemokine receptor CCR9 [ 20 23 ].…”
Section: Introductionmentioning
confidence: 99%